Comprehending testing of distributed embedded systems - Kilaru, Chaitanya; K RajaSekhara Rao, Dr (International Journal of Engineering and Technology, 2018)
It has been stated in the literature thata test case that needs to be used for testing a distributed embedded system be decomposed into elementary level test cases that can be tested at different computing locations of the system as conducting testing considering entire distributed system is complex as the reliability of testing depends on the environment setting made at each of the location and also the complexity of the communication interface established at each of the distributed location. There should be strategy for conducting testing at each of the locations and comprehend the results to provide wholesome working position of entire distributed embedded systems.In this paper, a strategy has been presented that explain how the testing can be undertaken at individual locations using different test methods and how the results are joined such that the final test results reflects the state of testing a distributed embedded system.Â